Upaya Meningkatkan Pemasaran Produk Rengginang - Artameilina, Elvinda; Islam, Muhammad Hifdil; Syuhri, Saifuddin (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to find out in detail about efforts to improve marketing of Rengginang products at Five Star MSMEs in Panarukan Situbondo. In this research, researchers used field study research. Field research used in qualitative research produces data which is interpreted as facts or information from actors (research subjects, information, actors, activities and places are the research subjects). Meanwhile, this type of research uses a case study type. A case study is part of a qualitative method that seeks to explore a particular case in more depth by involving the collection of various sources of information. This case study is a descriptive case study, that is, it aims to describe a fact or reality. The data source was obtained directly from the research location at Five Star UMKM Panarukan Situbondo through documents related to the problems studied. Apart from that, data was also obtained through interviews with the Chair of the MSME and several workers at the MSME. Once collected completely, it is then analyzed descriptively where specific conclusions are drawn from the general data that has been collected. The results of this research show that in general, efforts to increase the marketing of rengginang products are very effective because apart from having a permanent market, MSME managers are also taking strategic steps, namely by marketing online.